Laser Therapy of Glaucoma - Greenidge, Kevin C. (1983)
The introduction of argon-laser iridotomy and argon-laser trabeculoplasty have had a beneficial impact on the treatment of glaucoma. Recent attention has been given to complications of anterior segment laser therapy. Of most concern is an acute rise in intraocular pressure which may be as great as 20 mmHg. Since patients undergoing anterior segment laser therapy usually have pre-existing visual compromise, this rise in intraocular pressure may be detrimental. This pressure rise rarely requires surgery. Until long-term follow-up is available, and complications are better understood, these new treatment modalities should be employed with caution.